Pelatihan Pembuatan Kopi Kacang Kedelai Untuk Meningkatkan Ekonomi Masyarakat Desa Taman Cari - Harto; Diky Angga; Nurul Deswita Sari (Journal of Science and Social Development, 2025)
Abstract. This community service initiative aims to enhance the capacity of residents in Taman Cari Village through training on producing soybean-based coffee as an alternative product with added economic potential. The community faces limited knowledge and skills in processing soybeans beyond their basic use as food ingredients. The program was conducted through several stages, including preparation, training sessions, hands-on production practice, packaging workshops, and final evaluation. The outcomes indicate that participants acquired new skills in processing soybeans into a coffee-like beverage, improved their understanding of basic production standards, and developed simple product packaging suitable for small-scale marketing. This program is expected to contribute to increasing household income and encouraging the emergence of new micro-entrepreneurs within the village community. Keywords: soybean coffee, community empowerment, entrepreneurship training